Contributions of socio-demographic and psychosocial characteristics, functional status and physical activity level on prevalence of depressive symptoms among rural elderly in Johor state - Hamzah, Nur Aqlili Riana; Adznam, Siti Nur ‘Asyura; Mohd Taib, Mohd Nasir; Chan, Yoke Mun; Ibrahim, Zuriati; Azam, Syafinas (Nutrition Society of Malaysia, 2018)
Introduction: Depression and depressive symptom are common among the elderly. This study aimed to determine the influence of multiple factors and their correlations on the prevalence of depressive symptoms among elderly residents in selected FELDA schemes in Johor state. Methods: A total of 269 respondents were recruited through systematic sampling. Face-to-face interviews were conducted to obtain information on socio-demographic and psychosocial characteristics using pre-tested validated questionnaires; For functional status, the Lawton-IADL Scale was used to assess independent living skills; the Short Physical Performance Battery (SPPB) questionnaire was used to assess physical performance; cognitive function was assessed by the Hodkinson Abbreviated Mental Test (HAMT); physical activity level was determined using the Rapid Assessment of Physical Activity (RAPA); and depressive symptoms were assessed by the Geriatric Depression Scale-15. Results: Mean age of the respondents was 69.5±5.2 years. Prevalence of depressive symptoms was determined as 3.7%. Almost half (47.6%) were unable to perform one or more Lawton-IADL items, 30.9% had low physical performance, 15.6% had abnormal cognitive function and only 30.6% were physically active. There were significant correlations between the socio-demographic characteristics (age and monthly income; r=-0.135 and rs =-0.133 respectively; p<0.05), functional status and physical performance; r=-0.171 and rs =-0.194 respectively; p<0.01), and prevalence of depressive symptoms. Low physical performance contributed towards having depressive symptoms (β=-0.183; p<0.05). Conclusion: A relatively low prevalence of depressive symptoms was found among the elderly living in FELDA schemes in Johor. Low levels of physical performance was contributed towards prevalence of depressive symptoms among the elderly.